PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA POSTER TERHADAP PENGETAHUAN MANAJEMEN HIPERTENSI MASYARAKAT DI KELURAHAN TERNATE TANJUNG KOTA MANADO - Agust A. Laya; Kristine Dareda (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2022)
Hypertension or often also called high blood pressure can also be defined as persistent blood pressure, where the systolic pressure is above 140 mmHg and the diastolic pressure is 100 mmHg. In 2018 North Sulawesi was recorded as the first rank with hypertension sufferers with a total of 13.5% or around 315 thousand people and Manado City ranked second with the number of cases reaching 1,541. The purpose of this study is to find out whether there is an effect on health education by poster media on the knowledge of hypertension management in the community in the village of Ternate, Tanjung. The research design is using proposive sampling in determining the sample size, and finding a sample of 15 people to be taken and using the Mc Nemar test to get the results. This research is classified as a quasi-experimental pre and post test design. From the results using the McNemar test, it appears that there are changes before and after the counseling is given, where there are 11 people whose level of knowledge increases after being given counseling with a percentage of 73.3%. given health education with poster media in the kelurahan ternate tanjung and analyzed before and after the influence on public knowledge with poster media in the Kelurahan Ternate Tanjung.